CHARGED PARTICLE DYNAMICS IN TIME DEPENDENT MAGNETIC FIELDS - Machado, Jose Marcio [UNESP]; Tsuchida, Masayoshi [UNESP] (Inst Estudos Avancados-ieav, 2008)
In this work we study the behavior of charged particles immersed in a peculiar configuration of magnetic fields, which has a main constant field B(0) and a superimposed, transversal perturbation field B(1) sin(omega(p)t), with B(1) << B(0). By taking Cartesian coordinates and placing B(0) along the z axis and B(1) sin (omega(p)t) on the x axis, an analytical solution for y(t) may be obtained by solving an integrodifferential equation. Besides, the solution z(t) also exhibits a very interesting dynamics, and the entire system is conditioned by resonances between the particle orbit frequencies and the frequency of the magnetic transversal perturbation, omega(p). In this work we also discuss numerical simulations for the related particle trajectories, as well as potential applications in the context of separation phenomena.
Keywords: separation phenomena; resonances; magnetic fields